PERANCANGAN SISTEM INFORMASI AKUNTANSI PIUTANG BERBASIS WEB - Inggik Sri Cahayani; Rima Elya Dasuki (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
PT Galunggung Jaya is a company engaged in the industry that serves the deliveryof paper tube, paper core, paper cone, folding boards and corrugated boxes fordelivery to West Java and Central Java. This study aims to design a web - basedaccounts receivable accounting information system at PT Galunggung Jaya. Themethod used is interview and observation . The results of the research on thedesign of the accounts receivable information system to make it easier for adminsto record receivables that are more effective, precise, efficient and make it easierfor customers whose bills have passed the due date and can help companies inbuilding software that can minimize the possibility of data loss